Health Disparities Among Mid-to-Older Deaf LGBTQ Adults Compared with Mid-to-Older Deaf Non-LGBTQ Adults in the United States - Poorna Kushalnagar; Cara A. Miller (Health Equity, 2019)
Purpose: To compare chronic health and mental health conditions between mid-to-older deaf lesbian, gay, bisexual, transgender, and queer (LGBTQ) and mid-to-older non-LGBTQ adults who are 45 years or older. Methods: Medical conditions and mental health disorders data were gathered from 981 mid-to-older deaf adults (178 LGBTQ and 803 non-LGBTQ) who took the Health Information National Trends Survey in American Sign Language between 2015 and 2019. Modified Poisson regression with robust standard errors was used to calculate relative risk estimates and 95% confidence intervals for all medical conditions and mental health disorders with self-reported LGBTQ status as the main predictor, adjusting for known health correlates. Results: Consistent with the LGBTQ health disparity in the general population, our study findings indicated health disparities for certain medical conditions (e.g., lung disease, arthritis, and comorbidity) and mental health disorders (e.g., depression and anxiety) among mid-to-older deaf LGBTQ compared with non-LGBTQ deaf adults. Conclusion: Like the LGBTQ counterparts in the general population, deaf LGBTQ adults may require more frequent and comprehensive health care services. Culturally and linguistically competent care by providers may be invaluable in reducing such health inequities, particularly when provider education and training is undertaken through an intersectional framework that considers the interaction and context of multiple patient and provider social identities.